CENTRAL CORNEAL THICKNESS IN METABOLIC SYNDROME POPULATION, NON-METABOLIC SYNDROME POPULATION, AND DIFFERENT BODY MASS INDEX POPULATION - KHULUQI, ROFA HUSNUL; Handayani, Nina; Anandita, Nanda Wahyu (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesCentral corneal Thickness (CCT) is associated with many factors including systemic disease. Thisstudy aims to evaluate and compare the CCT values in Metabolic Syndrome (MS) population, Non-Metabolic Syndrome (non-MS) population, and all different Body Mass Index (BMI) population. MethodsThis population-based & community service-based cross sectional study, conducted on September-November 2019 in 3 rural areas of Malang. Written informed consent was obtained from all subjects.CCT was measured with ultrasound pachymeter. The diagnosis of MS was based on InternationalDiabetes Foundation 2006 criteria. Subjects were classified into 2 groups by MS and non-MS, alsostratifed by BMI, gender, and age. Differences in CCT value between groups based on MS & non-MS, BMI, age, and gender were analyzed. ResultsA total of 890 subjects aged ? 40 years old were included in this study, whereas 400 subjects werediagnosed as MS (44.9%) and 490 (55.1%) others as non-MS. Mean CCT of MS were significantlygreater than that of non-MS (549.743±43.22 ?m, P<0.05). Mean CCT of obese subjects weresignificantly greatest among other BMI groups (549.036±48.31 ?m, P<0.05). Mean CCT in womenwere significantly greater than that in men (546.268±39, P<0.05). Mean CCT of subjects aged 40–49years were significantly greatest among other age groups (551.278±33,33, P<0.05). ConclusionMS population had greater CCT value as compare to non-MS population. Obese population hadgreatest CCT value than overweight, normal, and underweight population. These findings may haveimplications for understanding the relationship between CCT changes and metabolic syndrome, aswell as BMI.